Phytoplankton Community Composition of Carigara Bay, Leyte and its Freshwater Tributaries - S, Hernando Alice Geraldine; Baldia, Susana F.; Jr., Paciente A. Cordero (Asian Journal of Biological and Life Sciences, 2020)
Carigara Bay is one of the acclaimed richer fishing waters in the entire Philippines because of its multi-gear fishery system. Filipinos living around the bay considered its marine life as one of their livelihood. However, the biodiversity of phytoplankton are still unexplored evident by the dearth of published data in scientific journals. Thus, this study was undertaken. Sampling was conducted on the five coastal towns surrounding the bay and its freshwater tributaries are Lindog and Bislig River found in Brgy. Uyawan and Bislig respectively situated in Carigara, Himanglos and Canomantag River in Brgy. Hilaba and Canomantag in Barugo, stream located in Brgy, Libertad, Capoocan, Caraycaray River and Lipasan Falls in Brgy. Caraycaray and Pinarigusan in San Miguel and Tula-an and Busay Falls in Brgy. Tula-an and Busay in Babatngon. Water samples were collected using a 2.5-3L Plexi glass sampler, transferred in three 1L cap bottle and brought in the laboratory for phytoplankton identification. Physico-chemical parameters were also gathered in all sampling sites to correlate with the phytoplankton density. Data were subjected to statistical analyses such as two way ANOVA. Results showed that there are three phyla quantified such as Bacillariophyta, Chlorophyta and Cyanophyta which are 44, 37 and 19% of the total phytoplankton. These were correlated with the physico-chemical parameters where in there was a significant positive correlation between water pH (r= 0.499;p= 0 .001), conductivity (r=0.519;p=0.001) and amount of phosphates (r= 0.446;p= 0.003) to the total cell density of all the three groups of phytoplankton identified.
Keywords: Bacillariophyta; Freshwater resources; Microalgae; Physico-Chemical parameters; positive correlation